Effect of smear layer deproteinizing on resin-dentine interface with self-etch adhesive - Ornnicha Thanatvarakorn (2018)
Objectives: This study aimed to investigate deproteinizing effect of sodium-hypochlorite (NaOCl) and mild acidic hypochlorous-acid (HOCl) pretreatment on smear layer-covered dentine and to evaluate their effects on morphological characteristics of resin-dentine interface with self-etch adhesive. Methods: Human coronal-dentine discs with standardized smear layer were pretreated with 6% NaOCl or 50 ppm HOCl for 15 s or 30 s. Their deproteinizing effects at the treated smear layer-covered dentine surfaces were determined by the measurement of amide:phosphate ratio using ATR-FTIR analysis. In addition, using TEM, micromorphological alterations of hybridized complex and nanoleakage expr ession were evaluated at the interface of a self-etch adhesive (Clearfil SE Bond) to the pretreated dentine surface with or without subsequent application of a reducing agent (p-Toluenesulfinic acid salt; Accel®). Results: Both pretreatments of NaOCl and HOCl significantly reduced the amide:phosphate ratio as compared with the no-pretreated group (p < 0.05), coincident with the elimination of the hybridized smear layer on their bonded interfaces. Nanoleakage within the hybrid layer was found in the no-pretreated and NaOCl-pretreated groups, whereas the subsequent reducing agent application changed the reticular nanoleakage to spotted type. HOCl-pretreated groups showed less nanoleakage expression in a spotted pattern, regardless of reducing agent application. Conclusions: NaOCl and HOCl solutions could remove the organic component on the smear layer-covered dentine, which could eliminate the hybridized smear layer created by self-etch adhesive, leading to the reduction of nanoleakage expression within hybrid layer. Clinical significance Smear layer deproteinizing could modify dentine surface, giving an appropriate substrate for bonding to self-etch adhesive system. © 2013 Elsevier Ltd. All rights reserved.